The other side of the story. Colonial politics still shape attitudes to language use in school in Africa. Contrast between South Africa and Mozambique - (:unkn) unknown (My University, 2013)
South Africa and Mozambique offer contrasting examples of attitudes to education language policy. Whereas in SA African languages are extensively used in primary grades, following previous policies, parents in general prefer to send their children to English-medium schools; in Mozambique, the recently introduced bilingual experimental program which for the first time gives recognition to local languages in schools triggers enthusiasm among rural communities. Colonial policies therefore seem to shape attitudes, if in reverse.
Keywords: African Research